2021
DOI: 10.21203/rs.3.rs-28486/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parental Communication On Sexual And Reproductive Health Issues To Their Adolescents And Affecting Factors At Asella Town, Ethiopia; A Community-Based, Cross-Sectional Study

Abstract: Background: Parents’ communication on sexual and reproductive health issues with their adolescent plays a great role in preventing morbidity and mortality associated with sexual behavior. However lack of parent to adolescent communication was a serious problem in Ethiopia resulted in teenage pregnancy, unsafe abortions, sexually transmitted infections, school problems, and other sexual risk behaviors. Parents have high responsibility on cultivating their son and daughter regarding to sexual and reproductive he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…The study found that respondents' attitudes significantly influenced their decision to use SRH services, with positive attitudes being five times more likely for women to use these services. This finding is consistent with studies conducted in South Ari and other countries, which indicated that individuals with positive attitudes towards SRH services were more likely to utilize them [38][39][40][41]. Positive attitudes can increase the demand for SRH services by encouraging individuals to seek medical attention and actively seek information about these services.…”
Section: Discussionsupporting
confidence: 90%
“…The study found that respondents' attitudes significantly influenced their decision to use SRH services, with positive attitudes being five times more likely for women to use these services. This finding is consistent with studies conducted in South Ari and other countries, which indicated that individuals with positive attitudes towards SRH services were more likely to utilize them [38][39][40][41]. Positive attitudes can increase the demand for SRH services by encouraging individuals to seek medical attention and actively seek information about these services.…”
Section: Discussionsupporting
confidence: 90%